Hydroelasticity and load alleviation of tidal current turbine blades - Lim, Jing Jie (2016)
Increasing demand for renewable energy has led to rapid developments in tidal power technologies. In this work, a hydro-servo-elastic model of a tidal current turbine is analysed and load alleviation methods implemented. The hydroelastic model uses a composite beam model coupled with a medium fidelity unsteady vortex-lattice method for hydrodynamics. The NREL 550kW tidal current turbine is simulated in a turbulent inflow field with a shear profile. Significant fluctuations in loads are found that may be detrimental to fatigue life of turbine blades. Passive and active load alleviation methods are implemented to reduce these fluctuations. Using passive bend-twist coupling, bending loads are significantly reduced by 23% spread across most frequencies. An active cyclic pitch control targeting the dominant load at 1P frequency resulted in a 24% reduction in root-bending moments. Although an active PID control was tested, the resulting 62.5% reduction in load was deemed unrealistic. Future tests are required to validate the results. The above work was also presented at the 3rd Asian Wave & Tidal Energy Conference (AWTEC) by the author.